Occupational therapy using a robotic-assisted glove ameliorates finger dexterity and modulates functional connectivity in amyotrophic lateral sclerosis - Yamakawa, Isamu; Yamada, Atsushi; Sonoda, Yuma; Wakita, Kiyoshi; Nishioka, Takashi; Harada, Yoshinori; Ogawa, Nobuhiro; Kitamura, Akihiro; Sanada, Mitsuru; Tani, Tohru; Imai, Shinji; Urushitani, Makoto (Journal of clinical neuroscience, 2023)
•The occupational therapy using a robotic-assisted glove improved hand dexterity in amyotrophic lateral sclerosis.•The robotic rehabilitation significantly improved both objective and subjective scores in amyotrophic lateral sclerosis.•The resting-state functional magnetic resonance imaging data analysis revealed that the robotic rehabilitation augmented brain functional connectivities. Although rehabilitation is recommended for amyotrophic lateral sclerosis (ALS), improvement of functional decline has hardly been achieved. We investigated the effect of occupational therapy that uses a robotic-assisted glove (RAG) on hand dexterity and the functional connectivities found in the brain of ALS patients. Ten patients diagnosed with ALS and admitted to the Shiga University of Medical Science (SUMS) Hospital from December 2018 to December 2021 participated in the study. These participants chose the hand side to wear RAG and exercised for two weeks. A sham movement was performed on the other side. We administered several functional assessments, including the Simple Test for Evaluating Hand Function (STEF), grip strength, pinch meter for grip strength, Canadian occupational performance measure (COPM), as well as nerve conduction study (NCS) before and after the exercise, and evaluated the results. We also analyzed six patients’ resting-state functional magnetic resonance imaging (rs-fMRI). Two-week robotic rehabilitation improved the STEF, grip strength, and COPM scores when compared with those of the other side. However, no significant effect was observed in the pinch meter and the NCS results. The rs-fMRI data analysis revealed that the robotic rehabilitation augmented two functional connectivities between the left pallidum-right supplementary motor cortex and right insular cortex-right sensorimotor network among the patients, which had beneficial effects. The occupational therapy using RAG displayed improved hand dexterity. The enhanced functional connectivities around the sensorimotor network might be associated with the improvement in hand dexterity because of the RAG.